SOME ISSUES OF IMPROVING THE LEGISLATION ON SMUGGLING (Proceedings of International Educators Conference, 2022)
This article discusses the occurrence of the crime of smuggling, the social need for liability for smuggling based on domestic and foreign experience. It also emphasizes the differences and similarities between smuggling and violation of customs legislation, some theoretical and practical issues related to the qualification of the crime of smuggling, developed recommendations and a proposal to improve the criminal law of the Republic of Uzbekistan.